The effectiveness of video modeling to reduce submissive behavior in intellectually disabled students who are victims of bullying in inclusive school - Ainun Alkaff; Noor Alkaff (Universitas Muhammadiyah Banjarmasin, 2024)
This study aimed to explore the effectiveness of video modeling in reducing submissive behavior in students with intellectual disabilities who have been victims of bullying in inclusive school. Submissive behavior, characterized by the inability to defend oneself or express opinions, often emerges when faced with stressful situations. Video modeling was used as an intervention to provide examples of assertive behavior that the students could imitate. This research employed a single-subject method involving a student with an intellectual disability identified as a victim of bullying. The student participated in six video modeling sessions depicting positive social interaction scenarios. Data was collected through direct observation, interviews, psychological tests, and informal assessments administered to teachers and parents. The analysis results showed a significant improvement in the student’s ability to express opinions and a reduction in submissive behavior. These findings indicate that video modeling can be an effective tool in supporting students with intellectual disabilities to overcome bullying and reduce submissive behavior in inclusive school environments.